Improving the management of the investment climate attractiveness (on the example of the Navoi FEZ) : “ИНВЕСТИЦИОН МУҲИТ ЖОЗИБАДОРЛИГИНИ БОШҚАРИШНИ ТАКОМИЛЛАШТИРИШ” - Rajabov, Nazirjon (Архив научных исследований, 2021)
The study of the essence, composition and evaluation criteria of the investment climate in the abstract, current trends in its management, investment potential and economic and legal status of free economic zones, scientific and methodological aspects of assessing the attractiveness of the investment climate, econometric models , Analyzed the factors affecting the investment potential of the Navoi FEZ and the effectiveness of their use. Zonal policy: prospects for effective management of the investment climate, the main directions of improving the attractiveness of the investment environment through the efficient use of resource potential and proposals and recommendations for managing investment potential through sustainability indicators.